Physical fitness of amateur paddle players: comparisons between different competitive levels - Camila Borges Müller; Fabricio Boscolo Del Vecchio (Desafio Singular, 2018)
Padel is widely practiced racket sport, although there is scanty data comparing competitive levels and differences between the sexes. Physical fitness of padel players was compared, according to sex and level. The research involved 35 people (age = 29.6 ± 2.9 years, practice = 6.8 ± 4.9 years), 13 of the first, 15 of the second and 7 of the third category. Aerobic power (PAM) with Yo-YoIR1, agility with handball agility specific test (HAST), muscular power with vertical jump and 3kg medicineball throw, and handgrip endurance strength (HES) with dynamometer were measured. The variables PAM, HAST, vertical jump, throttle and FIPM were significantly different between genders. In addition, in the male category, players in the upper category had lower heart rate scores after Yo-YoIR1 as well as distance traveled, throttle and FIPM maximum, while in females the superior category was better in the variables distance traveled in Yo-YoIR1 and vertical jump. On the other hand, in both sexes, players of superior categories presented greater time of practice. Amateur padel players with a higher competitive level do not present higher physical fitness, but present longer practice time.